2010
DOI: 10.4103/0253-7613.71898
|View full text |Cite
|
Sign up to set email alerts
|

Ruta graveolens L. toxicity in Vampirolepis nana infected mice

Abstract: Objective:To determine possible toxic effects of Ruta graveolens hydroalcoholic extract in gastrointestinal parasitic infection.Materials and Methods:A total of 100 g plant leaves and seeds were powdered and extracted with 1500 mL alcohol/water and administered by gavage to Swiss albino mice infected with Vampirolepis nana. Anti-parasitic evaluation and toxicity assays were carried out in six groups of ten animals each. Treatments were scheduled with both the leaves and the seeds’ extracts at doses of 2.5, 5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 19 publications
0
6
0
3
Order By: Relevance
“…Ruta graveolens is a medicinal plant that contains toxic substances. Several authors confirmed the toxicity, teratogenicity and abnormal embryo development of this herb [18][19][20]. A study by Hosseinzadeh et al [21] found that Salvia leriifolia Benth (Nuruzak) can exert significant decrease in weight and length of pregnant mice, as well as some limb abnormalities of fetuses.…”
Section: Discussionmentioning
confidence: 83%
“…Ruta graveolens is a medicinal plant that contains toxic substances. Several authors confirmed the toxicity, teratogenicity and abnormal embryo development of this herb [18][19][20]. A study by Hosseinzadeh et al [21] found that Salvia leriifolia Benth (Nuruzak) can exert significant decrease in weight and length of pregnant mice, as well as some limb abnormalities of fetuses.…”
Section: Discussionmentioning
confidence: 83%
“…The effect observed over vascular tone indicated a new role of the Ruta extract, however several reports indicated toxic effects of the extract in vivo models [15]. We explored the toxic effects of Ruta extract in the endothelial cellular model.…”
Section: Loss Viability With Ruta Extract In Crl1730 Cellsmentioning
confidence: 98%
“…The dry extract of the herb was prepared using a method described in a previous study (16). The MLE was placed in 500-mg capsules containing 250 mg of the dry extract of the herb and 250 mg of cornstarch as a filler.…”
Section: Herbal Drug Preparationmentioning
confidence: 99%